Immunity to Trichuris muris in the mouse - Roach, Tamara I. A. (1986)
Quantitative and qualitative analyses of the serum antibody responses of NIH, C57BL/10, BALB/c, DBA/2 and CFLP mice infected with Trichuris muris have been made using ELISA and immunoprecipitation techniques. No correlation was found between specific serum antibody titres measured using T. muris E/S products and the time of onset of expulsion in the different mouse strains examined. However, there were some differences in the antigen recognition profiles of some sera as determined by immunoprecipitation analyses. In all the strains of mice examined significant increases in detectable specific serum antibody to the parasite E/S products occurred around day 15 to 20 postinfection and continued to rise, as measured up to at least day 40 and even up to day 65. Cortisone acetate treatment during larval development, in infected CFLP mice, in order to establish heavy adult worm burdens, did not reduce specific antibody titres to T. muris E/S products. In responding and tolerant DBA/2 mice there was no marked difference in either the kinetics of specific serum antibody production during primary and secondary infections, or in the antigen specificities of secondary infection sera. The "defect" in mechanism in the tolerant DBA/2 mice, which allows primary infections of T. muris to develop to patency, was shown to be permanent as secondary infections with the parasite could also establish in these animals. An investigation was made of the phenomenon of tolerance in the DBA/2 model- system and in the cortisone treated CBA mice. The capacity of MLNC from different groups of animals to produce IL-2 in vitro upon mitogen stimulation was investigated, on the basis that IL-2 deficit during antigen presentation may result in immune tolerance. Although no differences were found in the responding and tolerant DBA/2 cell-Vpopulations, there was an apparently synergistic interaction between cortisone administration and T. muris infection which dramatically reduced the IL-2 producing capacity of the MLNC. However, IL-2 cannot yet be ruled out as a factor in the inherent tolerance of a proportion of the DBA/2 population as IL-2 receptor expression by the 2 groups of cells assayed was not examined. Basic analyses of the antigens of T. muris were performed. The major protein of adult male homogenate (AMA) was also the major protein of the excretory/secretory (E/S) products and the surface antigen preparations. In addition several common E/S and surface antigens were shown to have proteolytic enzyme activities against gelatin and/or casein. The relationship between T. muris and Trichinella spiralis was examined in greater detail, and the m. wts. of the cross-reacting antigens were determined. Evidence suggested that the stichosomes of these worms may be the source of these antigens. Both Trichuris muris adults and Trichinella spiralis infective larvae each had common major E/S and surface antigens, indeed, both were shown to have surface proteases. These studies were extended to examine the possibility of cross-reactivity between Trichuris muris and T. trichiura; mouse infection sera and human infection sera respectively were able to cross-react with heterologous antigen preparations. The demonstration that anti-Trichinella spiralis 48 kD and 50/55 kD stichocyte antigen MoAbs also reacted with Trichuris trichiura adult homogenate in ELISA supports the suggestion that common stichocyte antigens may exist amongst the trichuroid nematodes Trichuris muris, Trichuris trichiura and Trichinella spiralis. Monoclonal antibodies were produced against the E/S products of Trichuris muris, which were characterized in terms of isotype and antigen specificities. Initial experiments indicated that one of the IgA MoAbs recognizing 34,22,20 and 18 kD E/S proteins may be effective in the passive transfer of immunity.